Gestão de riscos na bovinocultura de leite no município Sant'ana do Livramento - (:unkn) unknown (Universidade Federal do Pampa, 2018)
Risk management is one of the important branches of management, in rural properties would not be different. The present work aims to understand how the risk perception is perceived with the dairy farmers of the municipality of Santana do Livramento, as well as what are the most relevant risk measures for them. The data were collected through semi-structured questionnaires, with the data listed through the Likert scale and analyzed using descriptive statistics. As a result producers tend to perceive more risks in environmental issues that surround them, political and climatological issues, but manage risks with greater attention to animal issues such as biological controls and special attention to climatic factors. And they perceive few risks in human, financial and technological matters, and give little relevance to financial management.
Keywords: Gestão de riscos; Bovinocultura de leite; Risk management; Cattle; CNPQ::CIENCIAS SOCIAIS APLICADAS